Methemoglobinemia and adverse events in Plasmodium vivax malaria patients associated with high doses of primaquine treatment (2009)
ABSTRACT: Primaquine (PQ) is recommended to prevent relapses in patients with Plasmodium vivax malaria infection. However, treatment with PQ causes methemoglobinemia. In this study, we measured the methemoglobin (MetHB) levels in three groups of subjects who received PQ treatment at 0.58, 0.83, or 1.17 mg/kg/d. A total of 112 subjects were studied. MetHB levels were detected at > 4% in 46–50% 1 day after PQ treatment in all three groups and 4–9% of subjects had MetHB levels > 4% 15 days after treatment. Only subjects receiving the highest doses of PQ had mild and brief adverse events, and 17% of them were associated with treatment. We conclude that when PQ is administered under certain conditions (i.e., normal glucose-6-phosphate dehydrogenase activity, in non-pregnant subjects and with a light meal), daily doses as high as 1.17 mg/kg do not represent a serious risk of high MetHB levels to patients.